Out-of-pocket Costs of Disabilities and Their Association with Household Socioeconomic Status Among School-aged Children in Vietnam - Pham, Hong-Luu (J Rural Med, 2013)
Objective: The aim of this study was to assess the economic burden of disability of school-aged children and to evaluate the association between disabilities and household socioeconomic status, as well as the economic burden of disability and household socioeconomic status in Vietnam. Materials and Methods: Nationally representative data for 9,882 children aged 6 to 17 years from the Vietnam Household Living Standard Survey 2006 were used. Disabilities were measured in six basic functional domains, including vision, hearing, remembering or concentrating, mobility, self-care, and communication. We evaluated the association between area, household income, educational attainment, or occupation of household head, and each difficulty. The ratio of health-care expenditure to per capita household income was compared by presence of a disability as well as household socioeconomic status. Results: The prevalence of difficulty was 1.9% for vision and 2.3% for at least one of the other five domains. Difficulty in vision was more prevalent in the richer households (p=0.001), whereas difficulty in the other five domains was more prevalent in the poorer households (p=0.002). The ratio of health-care expenditure to per capita household income was greater than 0.05 in 4.6% of children. The adjusted odds ratio of children with difficulty in vision having a health-care expenditure share greater than 0.05 compared with children without difficulty was 4.78 (95% CI: 2.95, 7.73; p<0.001), and that for difficulty in the other five domains was 3.13 (95% CI: 2.04, 4.80; p<0.001). Among children with difficulty in at least one of the five domains other than vision, the proportion of children with a health-care expenditure share greater than 0.05 was higher among children from the poorer households (p=0.033). Conclusions: Children with a disability spent more on health care relative to their income than those without. Visual disability was more prevalent among children from the richer households, whereas other disabilities were more prevalent among children from the poorer households.